Didactic conditions for formation of skills of conscious construction of image in beginning artists (Pedagogy of Higher and Secondary Education, 2009)
In the article the didactic terms of farming are examined conscious the prosess of construction of image the students of KHGF on the initial stage of study of picture.
Keywords: didactic terms; formoobracovame; perception; evident malerial; system of exercises